The association of a large-scale television campaign with exclusive breastfeeding prevalence in Vietnam - Nguyen, Tuan T.; Alayon, Silvia; Jimerson, Ann; Naugle, Danielle; Nguyen, Phuong Hong; Hajeebhoy, Nemat; Baker, Jean; Baume, Carol; Frongillo, Edward A. (American Public Health Association, 2017)
Objectives. To examine the association between exposure to breastfeeding television spots and exclusive breastfeeding (EBF).Methods. We performed face-to-face interviews with 11 722 mothers of infants younger than 6 months using 5 cross-sectional surveys 6 or more months apart between 2011 and 2014 in Vietnam. Sample sizes were 2065 to 2593, and approximately 50% of participants lived in areas with (Alive & Thrive [A&T]-intensive [I]) and approximately 50% without (A&T-nonintensive [NI]) facilities offering counseling services. We analyzed data at individual and commune levels separately for A&T-I and A&T-NI areas.Results. Exposure to television spots was associated with higher EBF in A&T-I (odds ratio [OR] = 3.33; 95% confidence interval [CI] = 2.70, 4.12) and A&T-NI (OR = 1.31; 95% CI = 1.03, 1.67) areas. In A&T-I areas, mothers who could recall at least 1 message were more likely to report EBF. In A&T-NI areas, only recall of at least 3 messages was associated with higher EBF. In communes, 1 message recalled (mean score range = 0.3–2.4) corresponded to 17 (P = .005) and 8 (P = .1) percentage points higher EBF prevalence in A&T-I and A&T-NI communes, respectively.Conclusions. Mass media should be part of comprehensive programs to promote EBF.